Third reported patient with RAP1B‐related syndromic thrombocytopenia and novel clinical findings. Issue 9 (22nd April 2022) - Miller, Dana; Saeed, Azhar; Nelson, Andrew C.; Bower, Matthew; Aggarwal, Anjali
Abstract: RAP1B is a RAS‐superfamily small GTP‐binding protein involved in numerous cell processes. Pathogenic gain‐of‐function variants in this gene have been associated with RAP1B ‐related syndromic thrombocytopenia, an ultrarare disorder characterized by hematologic abnormalities, neurodevelopmental delays, growth delay, and congenital birth defects including cardiovascular, genitourinary, neurologic, and skeletal systems. We report a 23‐year‐old male with a novel, de novo RAP1B gain‐of‐function variant identified on genome sequencing. This is the third reported case which expands the molecular and phenotypic spectrum of RAP1B ‐related syndromic thrombocytopenia.